2009
DOI: 10.1128/aem.01084-09
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Salmonella enterica in Leaves Is Induced by Light and Involves Chemotaxis and Penetration through Open Stomata

Abstract: Outbreaks of salmonellosis related to consumption of fresh produce have raised interest in Salmonella-plant interactions leading to plant colonization. Incubation of gfp-tagged Salmonella enterica with iceberg lettuce leaves in the light resulted in aggregation of bacteria near open stomata and invasion into the inner leaf tissue. In contrast, incubation in the dark resulted in a scattered attachment pattern and very poor stomatal internalization. Forcing stomatal opening in the dark by fusicoccin had no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
288
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(310 citation statements)
references
References 35 publications
14
288
1
7
Order By: Relevance
“…When studying the surface, high densities of bacteria were found, but both pathogens behaved similar and were never able to reach the parenchyma through the stomata, they were only found in the substomatal cavities. These results were expected as Kroupitski et al (2009a) showed already that internalization did not (often) occur in the dark or at low temperature for Salmonella. They reported internalization in around 10% of the observed fields both at low light (3 μE m −2 s −1 ) in combination with low storage temperature (4°C) and also when the lettuce was stored in the dark (at 30°F ig.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…When studying the surface, high densities of bacteria were found, but both pathogens behaved similar and were never able to reach the parenchyma through the stomata, they were only found in the substomatal cavities. These results were expected as Kroupitski et al (2009a) showed already that internalization did not (often) occur in the dark or at low temperature for Salmonella. They reported internalization in around 10% of the observed fields both at low light (3 μE m −2 s −1 ) in combination with low storage temperature (4°C) and also when the lettuce was stored in the dark (at 30°F ig.…”
Section: Discussionsupporting
confidence: 79%
“…internalization. Kroupitski et al (2009a) showed that the presence of exogenous nutrients can inhibit internalization as there is no need for the pathogens to search for other nutrients (Kroupitski et al, 2009a). Furthermore, we cannot exclude that the stomata were closed in the bag given the low metabolic state of the lettuce at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that E. coli O157:H7 is able to enter by natural openings in the plant surface, such as the sub-stomatal cavities in leaves (Brandl, 2008;Erickson, 2012;Kroupitski et al, 2009). Once the bacteria are inside the plant, following closure of the guard cells, they are protected from most superficial sanitisers (Gomes et al, 2009).…”
Section: Interacción E Internalización En Plantasmentioning
confidence: 99%